2016
DOI: 10.1007/s10517-016-3185-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic Evaluation of Dysfunction in the Erythron System of Experimental Animals during Modeling of Iron Deficiency Anemia in the Gestation Period

Abstract: We studied the dynamics of erythropoiesis in CBA mice during gestation against the background of treatment with iron-binding drug. The mechanisms of suppression of the bone marrow erythroid stem were evaluated. Administration of deferoxamine in a dose of 1 g/kg induced hypoplasia of the erythroid hemopoietic lineage. Suppression of bone marrow erythropoiesis manifested in a decrease of hemoglobin concentration and counts of reticulocytes, erythrocytes, and erythrokaryocytes. These changes were accompanied by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“… 47 Zhdanov et al demonstrated enhanced proliferative activity of erythroid precursors in bone marrow that was increased by concomitant administration of iron. 48 According to one theory, a population of primitive CD34 + progenitors responsible for cellular proliferation and regeneration is produced in maternal bone marrow in response to interaction with umbilical cord blood cells via immunologic signals. 49 Pregnancy is also sometimes accompanied by gestational thrombocytopenia and relative leukocytosis.…”
Section: Review Of Literaturementioning
confidence: 99%
“… 47 Zhdanov et al demonstrated enhanced proliferative activity of erythroid precursors in bone marrow that was increased by concomitant administration of iron. 48 According to one theory, a population of primitive CD34 + progenitors responsible for cellular proliferation and regeneration is produced in maternal bone marrow in response to interaction with umbilical cord blood cells via immunologic signals. 49 Pregnancy is also sometimes accompanied by gestational thrombocytopenia and relative leukocytosis.…”
Section: Review Of Literaturementioning
confidence: 99%